Relationship Of Health Service Quality With Bpjs Patient Satisfaction In The Outpatient Unit Lubuk Pakam Grandmed Hospital - Reni Aprinawaty Sirait; Silvia Indriani Simatupang (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2022)
The quality of health services reflects the improvement of health services in achieving patient satisfaction. Increased public awareness will encourage the demand for health services. These issues and some of the outstanding cases have created a public perception that there is a disparity in services for BPJS patients in general. The purpose of this study was to determine the relationship between the quality of health services with patient satisfaction BPJS card users at Grandmed Hospital. This type of research is an interpretive survey using a cross sectional approach. The sampling technique used is random sampling, which applies certain considerations in sampling. Service quality is a measure of how well the services provided meet customer (patient) expectations. In this study, a cross-sectional approach was used for analysis and investigation. The sample in this study were inpatients at Grandmed Lubuk Pakam Hospital with 32 respondents using the accidental sampling method using the chi square test using a 95% confidence level = (0.05). The results showed that there was still a significant relationship between services using grade 1 inpatient satisfaction where tangible p (0.038) < (0.05), reliability p (0.003) < (0.05), responsiveness p (0.026) < (0 ,05). ), guarantee p (0.002) <? (0.05) and feel p (0.005) <? (0.05). It is hoped that health workers will improve the quality of services provided, especially outpatient BPJS patients, apply smiles, greetings, speed, service schedules & punctuality in patient examinations so as to create interaction between patients and nurses. For hospital management, it is necessary to develop a information management system to facilitate services & matters of housing needs quickly.